Upgrading computer systems: one authority's experience. (Journal of Housing & Community Development)
The writer examines how the Columbus Metropolitan Housing Authority (CMHA) in Ohio upgraded its information system to use leading edge technology. According to Ron Lebsock, Management Information Systems Manager for the CMHA, the main reasons for changing the computer system were high costs of maintenance for the aging system, the desire to take advantage of UNIX-based technologies, and the desire to tap the pool of skilled mainstream computing personnel trained to work with UNIX. A secondary goal involved improving productivity and streamlining time-consuming agency processes. The reasons why CMHA considers the upgrade a success are outlined.